ADAMTS6: Emerging roles in cardiovascular, musculoskeletal and cancer biology - Mead, Timothy J. (Frontiers in Molecular Biosciences, 2022)
ADAMTS family members regulate mammalian development and disease, primarily through their function as proteases, by regulation of extracellular matrix composition. Until recently, ADAMTS6 was known as one of the orphan proteinases of the nineteen-member family with a relatively unknown expression pattern and function. Emerging focus on this enzyme has started to uncover these unknowns and revealed a vast importance and requirement of ADAMTS6 in cardiovascular and musculoskeletal development. In addition, ADAMTS6 has been linked to numerous disease settings including several types of cancer. This review summarizes the necessity of ADAMTS6 during development, its role in disease and requirement for essential prospective studies to fully realize its biological implications and potential for therapeutic intervention.